Sexual, reproductive health and health status of female sex workers in 12 Brazilian cities, 2016 - Letícia Penna Braga; Giseli Nogueira Damacena; Célia Landmann Szwarcwald; Mark Drew Crosland Guimarães (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objective: To investigate differences in sexual, reproductive health and health status indicators of female sex workers in 12 Brazilian cities. Methods: Cross-sectional study of biological and behavioral surveillance survey with a minimum sample of 350 female sex workers per city, recruited by respondent driven sampling, in 2016. Complex sample design was considered in the data analysis. Indicators and 95% confidence intervals related to sexual and reproductive health, and health status were described separately by city and for the total sample. Results: The total sample consisted of 4,328 female sex workers. The coverage of Pap smear exam, human immunodeficiency virus and syphilis tests and antenatal care indicators varied by 20 percentages points or more. Pap smear exam coverage ranged from 53.4% in Recife to 73.0% in Porto Alegre. The highest percentage of female sex workers who had never been tested for human immunodeficiency virus and syphilis was in Fortaleza (36.8 and 63.8%, respectively). Antenatal coverage ranged from 61.1% in Salvador to 99.0% in Curitiba. In five cities, the proportion of female sex workers who disclosed their sex work status in health services was over 20.0%. Conclusion: The differences between the indicators in the 12 cities followed the Brazilian population profile, with more vulnerable sex workers in the North and Northeast regions. The results show that it is essential to consider the barriers to accessing health, such as stigma and discrimination, which restrict the addressing of female sex workers specific needs.